2022
DOI: 10.1007/s11302-022-09854-6
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 receptor involved in antitumor activity of atractylenolide I in human cervical cancer cells

Abstract: Atractylenolide I (Atr-I) was found to sensitize a variety of human cancer cells in previous studies. Purinergic P2X7R plays important role in different cancers. However, whether Atr-I could generate antitumor activity in human cervical cancer cells and P2X7R get involved in this effect remain unclear. In this study, Hela (HPV 18 +) and SiHa (HPV 16 +) cells were treated with different doses of Atr-I. The results indicated that agonist and antagonist of P2X7 receptors, BzATP and JNJ-47965567 (JNJ), could suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…This might also incline us to test higher doses (over 4 mg/kg) of ATL I in future studies. Accumulating evidence has indicated that ATL I has a promising effect on cancer treatment, at least including colon cancer, cervical cancer, and breast cancer [53][54][55][56][57]. Thus, this also inclines us to explore the effect of ATL 1 on treating the later stages of metabolic-associated fatty liver disease, such as liver fibrosis, and even liver cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might also incline us to test higher doses (over 4 mg/kg) of ATL I in future studies. Accumulating evidence has indicated that ATL I has a promising effect on cancer treatment, at least including colon cancer, cervical cancer, and breast cancer [53][54][55][56][57]. Thus, this also inclines us to explore the effect of ATL 1 on treating the later stages of metabolic-associated fatty liver disease, such as liver fibrosis, and even liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The MPHs were extracted by an in situ two-step perfusion method, as previously reported [54]. In brief, mice were anesthetized with 10% chloral hydrate, and the limbs were fixed.…”
Section: Isolation Of Mouse Primary Hepatocytes (Mphs)mentioning
confidence: 99%
“…Moreover, other studies showed a decreased level of the full-length variant of the P2X7 receptor, where the level of reduction correlated with the degree of tumor development (Li et al, 2007). Similarly, in the two separate human cervical cancer cell lines, the P2X7 receptor would become engaged in the anticancer activity of atractylenolide-I (Han et al, 2022). There are also reports indicating the coexistence of different P2X7 receptor isoforms in cervical cancer cells, where an alternative P2XJ receptor splicing variant may form non-functional trimers with the P2X7A variant (Feng et al, 2006).…”
Section: P2x7 In Cervical Cancermentioning
confidence: 95%
“…By inhibiting the expression of Hsp27, ATL I can inhibit the proliferation of prostate carcinoma cells and enhance the efficacy of cabotinib [ 59 ]. Han et al [ 60 ] determined that ATL I decreased the proliferation of human cervical cancer cells Hela and SiHa, and that combination treatment with the P2X7R receptor antagonist JNJ increased cytostatic effect on SiHa cells.…”
Section: Pharmacological Effects Of Atractylenolidesmentioning
confidence: 99%